Variability of kernel morphological and flour physicochemical properties in tropical dent corn hybrids - BARIZA KHOIRUL HUMAM; WILLY BAYUARDI SUWARNO; MUHAMMAD AZRAI; ANDI TAKDIR MAKKULAWU; ROY EFENDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Humam BK, Suwarno WB, Azrai M, Makkulawu AT, Efendi R. 2023. Variability of kernel morphological and flour physicochemical properties in tropical dent corn hybrids. Biodiversitas 24: 1600-1609. Corn is an important crop worldwide for food, feed, and industry. The aims of this study were to study kernel morphological and corn flour physicochemical properties and hybrids selection according to nutritional values for food industries. Plant materials were 15 test hybrids and four check varieties, namely RK457, RK57, BISI18, and NASA29. Kernel morphological and corn flour physicochemical variations are influenced by kernel type. All dent hybrids had 40/0 mesh corn flour yielded significantly higher compared to NASA29. °Dent scores were negatively correlated to 40/0 mesh corn flour yields. The total and soluble carbohydrates of dent corn flour hybrids are significantly higher compared to semi-dent and semi-flint corn flour hybrids. According to corn flour nutritional values in polygon GT biplot analysis, dent hybrids had relatively high starch, total carbohydrate, and soluble carbohydrate contents. Semi-dent hybrids had relatively high moisture, crude protein, and total ash contents. Semi-flint hybrid had relatively high crude fat and crude fiber contents. Cluster-2 was dominated by dent hybrids according to the fuzzy clustering method and selected as potential hybrids. MSM53 was the female parent of dent hybrids in cluster-2. Potential hybrids could be evaluated further by corn flour functional properties analysis.